Time-Domain Characterization of Nematic Liquid Crystals Using Additive Manufacturing Microstrip Lines. - Mateos-Ruiz, Pablo; Pérez-Escribano, Mario; Hernández-Escobar, Alberto; Abdo-Sánchez, María Elena; Márquez-Segura, Enrique; Martín-Guerrero, Teresa María; Camacho-Peñalosa, Carlos (IEEE, 2024)
This paper presents a method for effectively characterizing the dielectric permittivity of nematic liquid crystals across a broad frequency range. These materials show significant potential for reconfigurable devices operating in microwave and millimeter-wave frequencies. To achieve this goal, an additive manufacturing technique is used to create a microstrip line that can be filled with liquid that acts as its substrate. The liquid crystal (LC) is then biased to modulate its permittivity. After manufacturing, a time-gating approach is used to extract the permittivity, eliminating the need for in-fixture calibration, such as Thru-Reflect-Line (TRL). Finally, the approach is validated through simulations and experimental results, which closely align with those reported using other methods in the bibliography.
Keywords: Cristales líquidos; Redes de banda ancha; Broadband measurements; Liquid crystals; Permittivity characterization; Reconfigurability; Time-gating